Fundamentals of instrumentation and measurement - Placko, Dominique (Instrumentation and measurement series., 2007)
Instrumentation and Measurement presents the general principles of instrumentation processes. The book explains the theoretical analysis of physical phenomena used by standard sensors and transducers to transform a physical value into an electrical signal. The preprocessing of these signals through electronic circuits - amplification, signal filtering and analogue to digital conversion - are then detailed, in order to provide useful basic information. The focus of the book moves on from elementary data to general complex systems. Topics covered include instrumentation and measurement chains, se.